GOODS AND SERVICES TAX & GOODS AND SERVICES TAX COUNCIL - Singh, Narendra Bahadur; Ankit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper examines the Goods and Services Tax (GST) introduced in India on 1st July 2017, which revolutionized the country's indirect tax system and reshaped Central-State relations. GST represents a significant shift from the prior tax regime, which had separate tax domains for the Centre (excise and service tax) and the States (VAT on sale and purchase of goods). The paper delves into the formation of the GST Council, a constitutional body established to oversee the implementation and administration of GST, comprising the Union Finance Minister, State Finance Ministers, and other key officials. The GST system, backed by the 101st Constitutional Amendment Act of 2016, aimed to create a unified market by replacing multiple tax layers with a single tax structure, thus facilitating seamless interstate commerce and fostering economic growth. It analyzes the GST Council's role in cooperative federalism, emphasizing how it navigates the balance of tax levying powers between the Centre and States. The paper also highlights key judicial pronouncements, which clarified the non-binding nature of the GST Council's decisions, emphasizing the council's recommendatory role. Furthermore, the paper explores the challenges and conflicts that have arisen, particularly around the compensation mechanism to States for revenue losses post-GST implementation and the Centre-State disputes regarding GST revenue distribution. It argues for the necessity of strong coordination and negotiation within the GST Council to maintain the unified tax system's integrity and ensure equitable revenue sharing, especially during crises like the COVID-19 pandemic. The GST's impact on fiscal federalism is significant, centralizing the tax regime and altering the financial autonomy of States. The paper concludes by discussing the need for ongoing reforms and adjustments to address the evolving economic landscape and ensure the GST system's long-term success.